Martinova učna pot kot medgeneracijski park v Kamnici (University of Maribor Press, 2020)
Martin’s Learning Path as an Intergenerational Park in Kamnica. The manual was prepared as part of the SIPK project entitled "Martin’s Learning Path as an Intergenerational Park in Kamnica". It deals with the conceptual design of the learning path in Kamnica. It includes a set of activities that participants can take on Martin’s learning journey. The planned learning path will emphasize the active learning of pre-school children and students of the Kamnica Primary School outside kindergartens and school. Designed as an intergenerational park, Martin’s Learning Path will also be intended for the wider social community.